HEAVY CLASTIC MINERALS AS A CRITERION FOR THE IDENTIFICATION OF ISLAND-ARC ENVIRONMENTS IN PALEOBASINS OF OROGENIC ZONES IN THE RUSSIAN FAR EAST - Markevich P.V.; Malinovsky A.I. (My University, 2006)
Island-arc environments in ancient basins, including forearc and backarc basins, are usually identified on the basis of the paleogeological position, structure, and composition of rock sequences, as well as the petrochemistry of volcanic and terrigenous rocks. We attempted to establish certain environments only based on heavy clastic minerals from sedimentary rocks of different (in structure and age) basins. The analysis of heavy mineral associations is a well-tested method for the establishment of provenances of clastic rocks.